2018
DOI: 10.3389/fmicb.2017.02616
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and Spatial Impact of Human Cadaver Decomposition on Soil Bacterial and Arthropod Community Structure and Function

Abstract: As vertebrate carrion decomposes, there is a release of nutrient-rich fluids into the underlying soil, which can impact associated biological community structure and function. How these changes alter soil biogeochemical cycles is relatively unknown and may prove useful in the identification of carrion decomposition islands that have long lasting, focal ecological effects. This study investigated the spatial (0, 1, and 5 m) and temporal (3–732 days) dynamics of human cadaver decomposition on soil bacterial and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 69 publications
2
39
0
Order By: Relevance
“…Only a few OTUs were present in both high-scavenging sites. We also examined the relative abundance patterns of OTUs classified as genera reported by previous studies to be associated with macroinvertebrates (Singh et al, 2018;Dharne et al, 2008;Gupta et al, 2011;Gupta et al, 2014;Lee et al, 2014;Shukla et al, 2017;Tóth et al, 2008;Weatherbee, Pechal & Eric Benbow, 2017). All macroinvertebrate-associated genera reached peak relative abundances during the later sampling periods except for Providencia and Myroides (Fig.…”
Section: Impact Of Scavenging On Bacterial Communitiesmentioning
confidence: 90%
“…Only a few OTUs were present in both high-scavenging sites. We also examined the relative abundance patterns of OTUs classified as genera reported by previous studies to be associated with macroinvertebrates (Singh et al, 2018;Dharne et al, 2008;Gupta et al, 2011;Gupta et al, 2014;Lee et al, 2014;Shukla et al, 2017;Tóth et al, 2008;Weatherbee, Pechal & Eric Benbow, 2017). All macroinvertebrate-associated genera reached peak relative abundances during the later sampling periods except for Providencia and Myroides (Fig.…”
Section: Impact Of Scavenging On Bacterial Communitiesmentioning
confidence: 90%
“…A change in the microbial community structure could also confer changes in microbial extracellular enzyme production and substrate use (Lerch et al, 2011;Singh et al, 2018), and therefore drive observed patterns of MBC 13 C under different environmental conditions found in coastal forests (Boschker et al, 1999;Wang et al, 2015). Soil organic C is also a complex mixture of organic compound classes, which exhibit a range of 13 C (Bowling et al, 2008), and therefore changes in the microbial community structure and/or enzyme capacity of the soil microbial community could alter microbial C substrate use and δ 13 C of microbial biomass.…”
Section: Discussionmentioning
confidence: 99%
“…For each biomass there was one fenced and one unfenced replicate located at least 100 m apart to exclude large scavengers and to reduce the likelihood of microbial crossover from other sites, and aid in the isolation of invertebrate communities (Fig. 1) [8]. Fencing was constructed with rolled wire fencing surrounding an area of approximately 2 m 2 , and each plot was further covered with a black plastic mesh.…”
Section: Methodsmentioning
confidence: 99%